Radiobrominated benzimidazole-quinoline derivatives as Platelet-derived growth factor receptor beta (PDGFRβ) imaging probes - Effendi, Nurmaya; Mishiro, Kenji; Takarada, Takeshi; Makino, Akira; Yamada, Daisuke; Kitamura, Yoji; Shiba, Kazuhiro; Kiyono, Yasushi; Odani, Akira; Ogawa, Kazuma (Scientific reports, 2018)
Platelet-derived growth factor receptor beta (PDGFRβ) affects in numerous human cancers and has been recognized as a promising molecular target for cancer therapies. The overexpression of PDGFRβ could be a biomarker for cancer diagnosis. Radiolabeled ligands having high affinity for the molecular target could be useful tools for the imaging of overexpressed receptors in tumors. In this study, we aimed to develop radiobrominated PDGFRβ ligands and evaluate their effectiveness as PDGFRβ imaging probes. The radiolabeled ligands were designed by modification of 1-{2-[5-(2-methoxyethoxy)-1 H - benzo[ d ]imidazol-1-yl]quinolin-8-yl}piperidin-4-amine ( 1 ), which shows selective inhibition profile toward PDGFRβ. The bromine atom was introduced directly into C-5 of the quinoline group of 1 , or indirectly by the conjugation of 1 with the 3-bromo benzoyl group. [ 77 Br]1-{5-Bromo-2-[5-(2-methoxyethoxy)-1 H -benzo[ d ]imidazol-1-yl]quinoline-8-yl}piperidin-4-amine ([ 77 Br] 2 ) and [ 77 Br]- N -3-bromobenzoyl-1-{2-[5-(2-methoxyethoxy)-1 H -benzo[ d ]imidazol-1-yl]quinolin-8-yl}-piperidin-4-amine ([ 77 Br] 3 ) were prepared using a bromodestannylation reaction. In a cellular uptake study, [ 77 Br] 2 and [ 77 Br] 3 more highly accumulatd in BxPC3-luc cells (PDGFRβ-positive) than in MCF7 cells (PDGFRβ-negative), and their accumulation was significantly reduced by pretreatment with inhibitors. In biodistribution experiments, [ 77 Br] 2 accumulation was higher than [ 77 Br] 3 accumulation at 1 h postinjection. These findings suggest that [ 76 Br] 2 is more promising for positron emission tomography (PET) imaging of PDGFRβ than [ 76 Br] 3 .